ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TERWUJUDNYA SEKOLAH ADIWIYATA MANDIRI DI SMA NEGERI 1 SUNGGAL KECAMATAN SUNGGAL - Fatmadhona Artamadya; Alvi Syahrin; Hesti Wahyuningsih (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2019)
The purpouse to analyze (1) The influence of policy factors (2) The influence of curriculum factor (3) The influence of factors of participation (4) The influence of facilities management factor .Determination of the number of samples using Slovin technique so as to obtain the number of samples of 92. The results showed   it can be concluded that simultaneous effect of environmentally sound policy variable, the implementation of environment-based curriculum and management of supporting facilities towards the realization of Adiwiyata Mandiri School at SMA Negeri 1 Sunggal Sunggal Subdistrict. (4) SMA Negeri 1 Sunggal does not have Adiwiyata Mandiri standard because the implementation of curriculum and policy has not been consistent and continuous. Keywords: Adiwiyata School, Adiwiyata School Factors